Effect of feeding on spawning of common carp - Mishra, Ashutosh; Singh, U P (Indian Journal of Fisheries, 2011)
The present investigation was carried out in four non-drainable rectangular ponds for observing maturation and spawning period of common carp. For satisfactory breeding of fish in confined water, feeding with suitable high energy diets rich in protein was supplied. For finding gonadal maturation, gonad weight, gonado - somatic index and fertilization rates were observed. The range of gonad weight and gonado-somatic index of male and female fish were 20.93 - 45.13 g and 10.92 - 12.09%, 28.95 - 60.1 g and 14.60 - 16.00% respectively. The fertilization rate was 73.57 - 82.00%. The study indicate that spawning and fertilization rate in common carp is affected by nutritious feeds rich in protein